Fresh produce supply chain management: overview of the proceedings and policy recommendations - Batt, Peter; Cadilhon, J. (Agricultural and Food Marketing Association for Asia and the Pacific-AFMA, Curtin University of Technology, Department of Agriculture, FAO, 2007)
Abstract is not available.